2015
DOI: 10.1007/s00418-015-1316-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting immunoreactivity in long-term storage of formalin-fixed paraffin-embedded tissue sections

Abstract: Antigen decay in archival formalin-fixed paraffin-embedded (FFPE) tissue sections for immunohistochemistry is a well-known phenomenon which may have repercussions on translational and research studies and length of storage time appears fundamental. The aim of this study was to evaluate all possible factors which may lead to antigen decay on a prospective standardized collection of human tissues with a panel of 14 routinely used antibodies. Serial slide sections from FFPE control tissues were stored using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 23 publications
4
68
0
Order By: Relevance
“…Grillo F et al demonstrated that antigen loss or decay was seen in IHC of CD3, CD 31, CD117, estrogen and progesterone receptors, Ki67, p53, TTF-1, vimentin, but not in IHC of smooth muscle actin, keratins 7, 20, AE1/AE3, 34βE12, and they also showed cold storage is suitable methods for long term storage of tissue sections. 19 The importance of cold storage (at minus degrees rather than at 4 o C) was reported by other researchers, 20 and these observations were consistent with our observation of figure 3.…”
Section: Discussionsupporting
confidence: 93%
“…Grillo F et al demonstrated that antigen loss or decay was seen in IHC of CD3, CD 31, CD117, estrogen and progesterone receptors, Ki67, p53, TTF-1, vimentin, but not in IHC of smooth muscle actin, keratins 7, 20, AE1/AE3, 34βE12, and they also showed cold storage is suitable methods for long term storage of tissue sections. 19 The importance of cold storage (at minus degrees rather than at 4 o C) was reported by other researchers, 20 and these observations were consistent with our observation of figure 3.…”
Section: Discussionsupporting
confidence: 93%
“…Following a recent study by our group,18 where decrease in signal intensity for Ki67 was noted when archival tissue was tested, possible methods for antigen recovery from old FFPE blocks were investigated. Similarly to what happens to sections stored on glass slides,13 the most superficial layers of the paraffin block may undergo the same processes of antigen loss. We have shown that antigen recovery may be possible if IHC is performed on sections collected after having discarded the first 500–1000 μm of tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The main and most explored cause of antigen decay, for IHC, is the storing of FFPE sections on glass slides and several reports have shown that section ageing (delay between cutting sections and IHC staining) and humidity can decrease antigenicity as early as 2 weeks after sectioning,10–12 while cold temperature storage of sections or paraffin blocks seem to be the best method for antigen preservation over time 13…”
Section: Introductionmentioning
confidence: 99%
“…All sections were used for immunohistochemistry within 1 month of cutting [14]. Immunohistochemistry was performed using the Ventana BenchMark® XT platform (Ventana Medical Systems, Oro Valley, Ariz., USA) automated immunostaining device, according to the manufacturer's protocol, using 3,3′-diaminobenzidine as chromogen.…”
Section: Methodsmentioning
confidence: 99%